Drugs with antidepressant properties affect tryptophan metabolites differently in rodent models with depression‐like behavior. Issue 1 (16th May 2017) - Eskelund, Amanda; Li, Yan; Budac, David P.; Müller, Heidi K.; Gulinello, Maria; Sanchez, Connie; Wegener, Gregers
Abstract: The metabolism of tryptophan through kynurenine and serotonin pathways is linked to depression. Here, effects of different drugs with antidepressant properties (vortioxetine, fluoxetine, and ketamine) on various tryptophan metabolites in different brain regions and plasma were examined using tandem mass spectrometry (LC‐MS/MS), in Flinders Sensitive Line rats, a genetic rat model of depression, and its controls: Flinders Sensitive Line and Sprague–Dawley rats. Protein levels of kynurenine pathway enzymes were measured in the brains and livers of these rat strains. Furthermore, effects of vortioxetine on tryptophan metabolites were assessed in the cortical regions of lupus mice (MRL/MpJ‐Fas Ipr ), a murine model of increased depression‐like behavior associated with inflammation. Sustained vortioxetine or fluoxetine (at doses aimed to fully occupy serotonin transporter via food or drinking water for at least 14 days) reduced levels of the excitotoxin quinolinic acid (QUIN) in various brain regions in all rats. Furthermore, chronic vortioxetine reduced levels of QUIN in MRL/MpJ‐Fas Ipr mice. Acute i.p. administration of fluoxetine (10 mg/kg) or vortioxetine (10 mg/kg) led to reduced brain 5‐hydroxyindoleacetic acid in Sprague–Dawley rats (2, 4, 6, and 8 h) and a similar trend was evident in Flinders Sensitive Line and Flinders Sensitive Line rats after 4 h. In contrast, single or repeated administration of ketamine (15 mg/kg i.p.) did not induce significant changes in metabolite levels. In conclusion, sustained vortioxetine and fluoxetine administration decreased QUIN independent of species, while ketamine was ineffective. These results support the hypothesis that modulating tryptophan metabolism may be part of the mechanism of action for some antidepressants. Abstract : The metabolism of tryptophan through kynurenine and serotonin pathways is linked to depression. Here, effects of different drugs with antidepressant properties (vortioxetine, fluoxetine, and ketamine) on various tryptophan metabolites in different brain regions and plasma were examined. Chronic antidepressant treatment reduced levels of the potential neurotoxin, quinolinic acid, in both brain and plasma of rats. Ketamine, acute or chronic treatment, had no robust effects on 13 tryptophan metabolites measured.